Identification of a novel RhlI/R-PrrH-LasI/Phzc/PhzD signalling cascade and its implication in P. aeruginosa virulence - Yang Lu; Honglin Li; Jieying Pu; Qian Xiao; Chanjing Zhao; Yimei Cai; Yuyang Liu; Lina Wang; Youqiang Li; Bin Huang; Jianming Zeng; Cha Chen (Emerging Microbes and Infections)
Small regulatory RNAs (sRNAs) act as key regulators in many bacterial signalling cascades. However, in P. aeruginosa, the sRNAs involved in quorum sensing (QS) regulation and their function are still largely unknown. Here, we explored how the prrH locus sRNA influences P. aeruginosa virulence in the context of the QS regulatory network. First, gain- and loss-of-function studies showed that PrrH affects pyocyanin, elastase and rhamnolipid production; biofilm formation; and swimming and swarming motility and impaired the viability of P. aeruginosa in human whole blood. Next, our investigation disclosed that LasI and PhzC/D were directly repressed by PrrH. In addition, RhlI, the key member of the rhl QS system, diminished the expression of PrrH and enhanced the expression of downstream genes. Bioinformatics analysis found two binding sites of RhlR, the transcription factor of the rhl system, on the promoter region of prrH. Further β-galactosidase reporter and qPCR assays confirmed that PrrH was transcriptionally repressed by RhlR. Collectively, our data identified a novel RhlI/R-PrrH-LasI/PhzC/PhzD regulatory circuitry that may contribute to P. aeruginosa pathogenesis. Our findings indicate that PrrH is a quorum regulatory RNA (Qrr) in P. aeruginosa and provide new insight into PrrH’s function.